The Fluidity of Monstrous and Chivalrous identities in Sir Gawain and the Carl of Carlisle and the Wedding of Sir Gawain and Dame Ragnelle - Özgün, Ulaş (Fırat University, 2025)
This study examines the fluid interplay between chivalrous and monstrous identities in Arthurian romances, using a framework drawn from monster studies, theories of evil and harm, performance studies, and postcolonial studies. Monstrosity is understood as a constructed and composite category. It is not an ontological category someone is but an epistemological category an agent becomes through reiterations of the collection of tangible and intangible signifiers that validate the subject’s coming into being within a particular discursive system. In the Arthurian romances, the discursive normality is framed through the regulating codes of chivalry. Monsters are beings whose performance of transgressive acts inflict various forms of undeserved harm to chivalry, others, or society in general. The article explores this porosity in Sir Gawain and the Carl of Carlisle (c. 1400) and The Wedding of Sir Gawain and Dame Ragnelle (c. 1500). It argues that in these stories, knights and their adversaries exist in a fluid state, constantly shifting between chivalrous and monstrous identities based on their actions in confrontations. These encounters highlight how chivalric and monstrous identities are not fixed but are shaped through performative acts and cultural constructs, leading to conflict within these narratives. Thus, Arthurian knights risk embodying monstrosity when they engage in behaviors that deviate from, threaten, or harm the core values of the chivalric society they uphold.

Bu çalışma, Arthur romanslarında şövalye ve canavar kimlikleri arasındaki geçirgen ilişkiyi, canavar çalışmaları, kötülük ve hasar teorileri, performans çalışmaları ve postkolonyal çalışmalar gibi çeşitli akademik alanlardan yararlanan metodolojik bir çerçeve kullanarak incelemektedir. Canavarlık, inşa edilmiş ve bileşik bir kategori olarak anlaşılmaktadır. Böylece, canavarlık, birinin ontolojik olarak sahip olduğu bir kategori değil, bir failin belirli bir söylemsel sistem içinde varlığının doğrulanmasını sağlayan somut ve soyut göstergelerin tekrarı yoluyla olduğu bir epistemolojik kategoridir. Arthur romanslarında, normallik söylemi şövalyelik düzenini belirleyen kurallarla çerçevelenir. Canavarlar, şövalyeliğe, başkalarına veya genel olarak topluma çeşitli biçimlerde haksız zararlar veren, kurallara aykırı eylemler gerçekleştiren varlıklardır. Makale, bu geçirgenliği Sir Gawain and the Carl of Carlisle (yak. 1400) ve The Wedding of Sir Gawain and Dame Ragnelle (yak. 1500) eserlerinde incelemektedir. Bu hikayelerde şövalyelerin ve düşmanlarının, karşılaşmaları sırasında davranışlarına göre sürekli olarak şövalye ve canavar kimlikler arasında geçiş yaptığı savunulmaktadır. Bu karşılaşmalar, şövalyelik ve canavar kimliklerin sabit olmadığını, edimsel ve kültürel yapılar aracılığıyla şekillenerek anlatılar içinde çatışmaya yol açtığını vurgulamaktadır. Böylece Arthur şövalyeleri, şövalyelik toplumunun köklü değerlerini tehdit eden veya zarar veren davranışlarda bulunduklarında canavar figürlerine dönüşme riski taşır.
Sir Gawain and the Carl of Carlisle ve the Wedding of Sir Gawain and Dame RAgnelle’de Canavar ve Şövalye Kimliklerinin Geçirgenliği
Keywords: Medieval Literature; Ortaçağ Edebiyatı